Hubungan Tingkat Pengetahuan Dengan Perilaku Masyarakat Dalam Mengelola Obat Rusak Dan Kedaluwarsa Di RW 009 Desa Sukaragam - Fajar Amirulah (UNIVERSITAS MUHAMMADIYAH MATARAM, 2023)
In everyday life, people using and storage the medicines at home for self-medication. Of the stored drugs, some drugs are unused properly and to much only stored for a long period of time, causing damage to the drugs and the drugs accumulates to the limit of expiration. The aims of this study to analyze the relationship between the level of knowledge and the behavior of the people of RW 009 Sukaragam Village in managing destructive drugs and expired drugs at home. This research type a analytic survey research with a Cross Sectional observational design approach which was carried out in the community of RW 009 Sukaragam Village. The method of sampling used is Cluster Sampling. The sample size of 91 was calculated use the Slovin formula with a precision of 10% (0,1). The instrument used a questionnaire. The research was conducted from March-May 2022. In the results of data analysis, respondents with good knowledge category were 29 (31,9%), enough 44 (48,4%) and 18 (19,8%) less and respondents with positive behavior category 65 (71,4%), negative 26 (28,6%). In the results of bivariate data analysis using the Chi Square test, the results obtained p-value 0.064 (p-value >0.05), then the interpretation used is Ha is rejected and H0 is accepted. Based on this research, it can be concluded that there is no significant relationship between the level of knowledge and community behavior in managing damaged and expired drugs in RW 009 Sukaragam Village.